2013
DOI: 10.1530/rep-13-0100
|View full text |Cite
|
Sign up to set email alerts
|

The role of prion protein in stem cell regulation

Abstract: Cellular prion protein (PrP C ) has been well described as an essential partner of prion diseases due to the existence of a pathological conformation (PrP Sc ). Recently, it has also been demonstrated that PrP C is an important element of the pluripotency and self-renewal matrix, with an increasing amount of evidence pointing in this direction. Here, we review the data that demonstrate its role in the transcriptional regulation of pluripotency, in the differentiation of stem cells into different lineages (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 81 publications
1
12
0
3
Order By: Relevance
“…In fact, although highly concentrated within the CNS, this membrane-bound extracellular glycoprotein, is ubiquitous in humans and extremely conserved throughout the evolution. In this context, several studies proposed that PrP C is involved in the regulation of stem cell self-renewal, proliferation and differentiation [64, 65]. Moreover, more recently it was suggested that PrP C might also promote human tumor development and diffusion, and the induction of drug resistance [22, 36].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although highly concentrated within the CNS, this membrane-bound extracellular glycoprotein, is ubiquitous in humans and extremely conserved throughout the evolution. In this context, several studies proposed that PrP C is involved in the regulation of stem cell self-renewal, proliferation and differentiation [64, 65]. Moreover, more recently it was suggested that PrP C might also promote human tumor development and diffusion, and the induction of drug resistance [22, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, early developmental arrests were described in PrP knock out models of zebrafish 9 supporting the role of PrP C in early development in at least one taxonomic class. The recent article by Miranda et al provides comprehensive review of the studies on the role of PrP C in stem cell pluripotency, self-renewal and differentiation, 53 therefore we will only discuss the results that are the most relevant to the current finding. During early embryogenesis, PrP C expression was found to be largely limited to cells that undergo neural differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian prions share many common features with their counterparts in yeast, but their function and patterns of inheritance are less well known. Nevertheless, they have been shown to regulate pluripotency in mouse embryonic cells and contribute to their differentiation into neural progenitor cells (Peralta et al 2011;Miranda et al 2013). Importantly, normal PrP (PrP C ) are also present in bovine oocytes and pre-elongation embryos (Peralta et al 2012), although again their function is poorly understood.…”
Section: Inter(trans)generational Inheritancementioning
confidence: 99%